Plant Cell and Tissue Cultures – A Page in the History of Biology in Romania - GHIORGHIȚĂ, Gogu (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Four decades have passed since a new research field started being promoted in Romania: in vitro cell and tissue cultures of plants.This paper highlights the outstanding contribution to its development made by a reputed specialist – Dr. Dorina Cachiță, the pioneer in this field in our country. Moreover, the paper presents the social and economic context at the time this domain was launched, the difficulties in promoting it, it describes the author’s beginnings and personal achievements together with the ones of his research group in the field of in vitro plant culture. On the whole, the article represents a page in the history of Romanian biology in Romania and is dedicated to the honour of PhD Prof. Dorina Cachiță.